A Carbon 21 Steroidal Glycoside with Pregnane Skeleton from Cynanchum atratum Bunge Promotes Megakaryocytic and Erythroid Differentiation in Erythroleukemia HEL Cells through Regulating Platelet-Derived Growth Factor Receptor Beta and JAK2/STAT3 Pathway - Jue Yang; Chaolan Pan; Yang Pan; Anlin Hu; Peng Zhao; Meijun Chen; Hui Song; Yanmei Li; Xiaojiang Hao (MDPI AG, 2024)
Erythroleukemia is a rare form of acute myeloid leukemia (AML). Its molecular pathogenesis remains vague, and this disease has no specific therapeutic treatments. Previously, our group isolated a series of Carbon 21 (C-21) steroidal glycosides with pregnane skeleton from the root of Cynanchum atratum Bunge. Among them, we found that a compound, named BW18, can induce S-phase cell cycle arrest and apoptosis via the mitogen-activated protein kinase (MAPK) pathway in human chronic myeloid leukemia K562 cells. However, its anti-tumor activity against erythroleukemia remains largely unknown. In this study, we aimed to investigate the anti-erythroleukemia activity of BW18 and the underlying molecular mechanisms. Our results demonstrated that BW18 exhibited a good anti-erythroleukemia activity in the human erythroleukemia cell line HEL and an in vivo xenograft mouse model. In addition, BW18 induced cell cycle arrest at the G2/M phase and promoted megakaryocytic and erythroid differentiation in HEL cells. Furthermore, RNA sequencing (RNA-seq) and rescue assay demonstrated that overexpression of platelet-derived growth factor receptor beta (PDGFRB) reversed BW18-induced megakaryocytic differentiation in HEL cells, but not erythroid differentiation. In addition, the network pharmacology analysis, the molecular docking and cellular thermal shift assay (CETSA) revealed that BW18 could inactivate Janus tyrosine kinase 2 (JAK2)/signal transducer and activator of transcription 3 (STAT3) pathway, which might mediate BW18-induced erythroid differentiation. Taken together, our findings elucidated a novel role of PDGFRB in regulating erythroleukemia differentiation and highlighted BW18 as an attractive lead compound for erythroleukemia treatment.